2019
DOI: 10.31925/farmacia.2019.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Contributions on Formulation and Preliminary Evaluation of Ocular Colloidal Systems of Chitosan and Poloxamer 407 With Bupivacaine Hydrochloride

Abstract: The aim of this paper was the formulation and preliminary evaluation of colloidal systems with improved mechanical and mucoadhesive properties in order to increase ocular retention time and drug bioavailability. Polymeric mixtures of chitosan (0.3%), a pH-sensitive polymer, and poloxamer 407 (12%, 15%, 18%), thermoresponsive polymer, with bupivacaine hydrochloride (0.25%) were prepared. Gelling temperature, wettability, rheological behaviour and in vitro drug release were evaluated. The formulation containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Irimia et al have reported in situ gelling P407/CS formulations for the ocular delivery of bupivacaine hydrochloride, which is used as a topical anesthetic [235]. A series of P407/CS dispersions with various poloxamer concentrations were prepared by the "cold method".…”
Section: Non-ionic Polymersmentioning
confidence: 99%
“…Irimia et al have reported in situ gelling P407/CS formulations for the ocular delivery of bupivacaine hydrochloride, which is used as a topical anesthetic [235]. A series of P407/CS dispersions with various poloxamer concentrations were prepared by the "cold method".…”
Section: Non-ionic Polymersmentioning
confidence: 99%
“…Rheological evaluation was performed for the most representative systems, offering information concerning the phase behaviour, the quality profile and the flow characteristics according with their composition. Thus, MEAS 1 -MEAS 3 microemulsions were evaluated at 23 ± 0.5°C using Multi Visc rheometer (Fungilab SA, Barcelona, Spain), equipped with an LCP spindle, as it was previously reported [26].…”
Section: Physical Characterization Of Microemulsionsmentioning
confidence: 99%
“…The recommended dose for Ripasudil 0.4% is one drop twice a day in the long term for patients with glaucoma or intraocular hypertension. According to specialized studies to date it has been observed that the drug administered alone decreases IOP by about 3.5 mmHg (2.6 mmHg -3.7 mmHg), administered in combination with a prostaglandin analogue decreases the additional IOP by approximately 3.2 mmHg and when supplemented with a beta-blocker treatment decreases the IOP by approximately 2.9 mmHg in addition [20,[36][37][38][39]92]. The side effects of Ripasudil documented in the literature were: blepharitis, allergic conjunctivitis, conjunctival hyperaemia and punctate keratitis, transient symptoms that appear to have been dose dependent.…”
Section: Rock Inhibitors and Glaucomamentioning
confidence: 99%